A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages hospital service shall be entrusted to new joint authorities, which will be formed by combining for the purpose the existing county and county borough councils in joint boards operating over areas to be settled by the Minister after consultation with local interests at the outset of the scheme. There will be some exceptional cases (the County of London is the most obvious) where combination will be unnecessary. The powers and duties of present public hospital authorities will be transferred to the joint authorities, who will take over the ownership and management of all publicly owned hospitals. An area hospital plan The first task of each new joint authority will be to assess the hospital needs of its area and the available hospital resources, and to work out a plan of hospital arrangements for the area, based on using, adapting and where necessary supplementing the existing resources. All this will be done in consultation with local professional opinion and other local interests, including the voluntary hospitals. The plan will then be submitted to the Minister for approval and will have no validity until so approved. The approved plan will define the parts to be played by the various hospitals, both the hospitals of the joint authority and the voluntary hospitals. Voluntary hospitals will not be compelled to participate in the plan, but the Government trust that they will not hesitate to do so since their collaboration will be of great importance to the success of the new hospital service. Indeed, without this collaboration it would be many years before the new joint authorities could build up a system adequate for the needs of the whole population. Voluntary hospitals Where a voluntary hospital agrees to participate in the new service, its participation will rest on a contract with the joint authority under which the hospital will undertake to provide the services specified in the area plan, and to abide by conditions applying to all hospitals and settled centrally for the country as a whole. A voluntary hospital accepting these arrangements will receive certain service payments from the joint authority — these service payments being in accord with centrally determined scales, and being less in amount than the total cost of the service rendered (for if the voluntary system is to be maintained, the voluntary hospital will still rely in large measure on its own resources, personal benefaction and on the continuing support of all who believe in the voluntary hospital movement). It will also receive from central funds certain payments in respect of its help in the scheme — payments which can, if the hospitals wish, be pooled in one fund from which the actual distribution to each hospital can take account of its particular needs. There will be no question of any interference in the internal management of voluntary hospitals, of the surrender by them of their independence and autonomy, or of any change in their status. The Government will discuss their proposals in detail with repre- 14 36/H24/41